2015
DOI: 10.1007/s13402-015-0248-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ras-mediated signaling pathways in CML stem cells

Abstract: A closer investigation of the influence of Ras-mediated signaling pathways on CML progression to blast crisis is warranted to uncover new directions for targeted therapies, particularly in cases that are resistant to current tyrosine kinase inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 104 publications
0
10
0
Order By: Relevance
“… 17 MAPK pathway has been recognized as one of the most important pathways involved in the development of cancers, especially leukemias. 18 …”
Section: Vitamin D and Gene Regulationmentioning
confidence: 99%
“… 17 MAPK pathway has been recognized as one of the most important pathways involved in the development of cancers, especially leukemias. 18 …”
Section: Vitamin D and Gene Regulationmentioning
confidence: 99%
“…A recent assessment of CML mouse models and patient-derived stem cells has revealed that CML-derived stem cells may not be dependent on the presence of BCR-ABL for their survival. These data suggest that therapeutic approaches should also be aimed at targeting BCR-ABL independent mechanisms governing LSC resistance and survival [158, 159]. …”
Section: Targeting Leukemia Stem Cellsmentioning
confidence: 99%
“…19 Activating mutations or Ras gene amplification is observed in nearly a third of human cancers. 20 These mutations lead to non-ligand-dependent activation of signaling pathways, leading to increased cell proliferation. Mutations involving Ras gene mutations, most notably NRAS, are observed in 5-10% of MDS patients; however, the prevalence of this mutation is up to 30% in patients with isolated isochromosome 17 [i (17q)].…”
Section: Genetic and Epigenetic Abnormalitiesmentioning
confidence: 99%